Attitude towards transgression of social norms and family transgenerational history in inmates sentenced from a correctional facility - Venturo De La Cruz, Carlo André (2019)
The present investigation had as final purpose to determine the existing relation between the Attitude towards the Transgression of Social Procedure and the Transgeneracional Familiar History in prisoners sentenced of a penitentiary establishment. With sample of 337 prisoners sentenced with three types of committed crime: aggravated Theft, Homicide and sexual Violation, all of masculine gender and with sentences in process. For the investigation two instruments constructed by Solari (2016) were in use: Scale of attitude towards the transgression of social procedure (AHTOS) and the Questionnaire of History Transgeneracional Familiar (HTRAFA). The results show a correlation and significant of direct, low type (rho =.113) and (p = .038 < alpha = .05). Likewise, there were correlated the dimensions of the variable Attitude towards the transgression of social procedure and the indicators of the History familiar Transgeneracional.